Beispiel Nr: 05
$ \text{Gegeben:} \\ \vec{a}=\left( \begin{array}{c} a_1 \\ a_2 \\ a_3 \\ \end{array} \right)\qquad \vec{b}= \left( \begin{array}{c} b_1 \\ b_2 \\ b_3 \\ \end{array} \right) \qquad \vec{c}= \left( \begin{array}{c} c_1 \\ c_2 \\ c_3 \\ \end{array} \right) \\ \text{Gesucht:} \text{Spatprodukt,lineare Abhängigkeit,Basisvektoren} \\ \\ \textbf{Gegeben:} \\ \vec{a} =\left( \begin{array}{c} 1 \\ 0 \\ 1 \\ \end{array} \right) \qquad \vec{b}= \left( \begin{array}{c} 0 \\ 2 \\ 0 \\ \end{array} \right)\qquad \vec{c}= \left( \begin{array}{c} 4 \\ -6 \\ 4 \\ \end{array} \right) \\ \\ \textbf{Rechnung:} \\ \vec{a}= \left( \begin{array}{c} 1 \\ 0 \\ 1 \\ \end{array} \right) \qquad \vec{b}= \left( \begin{array}{c} 0 \\ 2 \\ 0 \\ \end{array} \right) \qquad \vec{c} = \left( \begin{array}{c} 4 \\ -6 \\ 4 \\ \end{array} \right) \\ V=\left|\begin{array}{ccc} 1\ & 0 & 4\\ 0& 2 & -6\\ 1& 0 & 4 \\ \end{array}\right| \begin{array}{cc} 1\ & 0 \\ 0& 2 \\ 1& 0 \end{array} \\ V=1 \cdot 2 \cdot 4+ 0 \cdot \left(-6\right) \cdot 1 + 4 \cdot 0 \cdot 0 \\ - 4 \cdot 2 \cdot 1 - 1 \cdot \left(-6\right) \cdot 0 - 0 \cdot 0 \cdot 4 \\ V=0 \\ \text{ Die 3 Vektoren sind linear abhängig - komplanar} $